Isolation and characterization of an antinociceptive compound from crotalus durissus terrificus venom - Angstmam, Davi Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Pain is a sensation related to current or potential tissue damage and may be associated with the symptom of a disease or defined as the disease itself, in the case of chronic pain. The most recommended treatment of pain, especially physical pain, is analgesics. However, the use of these medications presents adverse effects such as tolerance and dependence when used continuously. One of the alternatives for the development of new drugs is to invest in studies of the toxinology of animal venoms. The present study aimed to isolate and characterize a low molecular weight molecule present in the venom of Crotalus durissus terrificus (C.d.t.) and to evaluate its potential antinociceptive effect. For this purpose, purification and isolation methods by HPLC-RP were used, followed by biological tests such as the formalin test, tail flick and rota-rod, in order to find a molecule with the respective property. The methods used to separate the low-mass components were effective and it was possible to identify a compound in the C.d.t venom with an approximate molecular mass of 412 Da, which presented anti-inflammatory and analgesic activity by oral and intraperitoneal routes. Future tests should be performed to identify its mechanism of action, as well as to evaluate possible toxic and side effects.
Isolamento e caracterização de um composto antinociceptivo do veneno de Crotalus durissus terrificus
Keywords: Crotalus; Veneno; Analgésicos